2000
DOI: 10.1073/pnas.97.3.1101
|View full text |Cite
|
Sign up to set email alerts
|

Mouse VAP33 is associated with the endoplasmic reticulum and microtubules

Abstract: VAMP/synaptobrevin is a synaptic vesicle protein that is essential for neurotransmitter release. Intracellular injection of antisera against the Aplysia californica VAMP/synaptobrevin-binding protein ApVAP33 inhibited evoked excitatory postsynaptic potentials (EPSPs) in cultured cells, suggesting that this association may regulate the function of VAMP/synaptobrevin. We have identified and characterized a mouse homologue of ApVAP33, mVAP33. The overall domain structure of the proteins is conserved, and they hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
114
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 43 publications
4
114
0
1
Order By: Relevance
“…These diverse functions have been demonstrated in different species and cell types, and are mediated by different members of this family. Nevertheless, the overall structures of VAP proteins are similar and consist of a large N-terminal region facing the cytoplasm and a hydrophobic C terminus that functions as a transmembrane domain (TMD) (20). The cytoplasmic region contains a conserved N-terminal domain of 100 amino acids, which shares high sequence similarity with the nematode major sperm protein (MSP).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These diverse functions have been demonstrated in different species and cell types, and are mediated by different members of this family. Nevertheless, the overall structures of VAP proteins are similar and consist of a large N-terminal region facing the cytoplasm and a hydrophobic C terminus that functions as a transmembrane domain (TMD) (20). The cytoplasmic region contains a conserved N-terminal domain of 100 amino acids, which shares high sequence similarity with the nematode major sperm protein (MSP).…”
mentioning
confidence: 99%
“…Subsequent studies demonstrated the interaction of the mammalian VAP-A with additional SNAREs, including syntaxin 1A, rbet1, rsec22, ␣SNAP, and NSF (29). VAP-A also interacts with the tight junction protein occludin (22), with microtubules (20,24), and with OSBP (oxysterol-binding protein) (28). In this study, we isolated VAP-B as an interacting protein with Nir2, using a pull-down experiment and mass spectrometry analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicle-associated membrane protein-associated protein A (VAPA) 3 is an endoplasmic reticulum (ER)-resident type II transmembrane protein with homologs widely distributed from yeast to human (1)(2)(3). Recently, evidence has accumulated that in mammalian cells VAPA participates in the regulation of inter-organelle transport of membrane lipids by recruiting lipid transfer proteins to the ER membrane.…”
mentioning
confidence: 99%
“…First, VAP-A is known to play an important role in mediating cellular exocytosis in numerous cell types, including SMCs (Sollner et al, 1993;Skehel et al, 1995Skehel et al, , 2000Sudhof, 1995;Rothman and Sollner, 1997;Weber et al, 1998;Weir et al, 2001). A variety of studies indicate that SMCs are capable of responding to and modifying their microenvironment by the secretion of cytokines, growth factors, and extracellular matrix (Simon-Assman et al, 1990Burgess and Sizeland, 1990;Simo et al, 1991;Perr et al, 1992; One such transcript, identified as T2 (arrowhead), was differentially expressed in immature smooth muscle myocytes in three separate reactions composed of multiple concentrations of distinct tcRNA preparations both in the presence and absence of DNAse 1.…”
Section: Discussionmentioning
confidence: 99%